coliBASE: an online database for Escherichia coli, Shigella and Salmonella comparative genomics - Chaudhuri, Roy R. (Oxford University Press, 2004)
We have constructed coliBASE, a database for Escherichia coli, Shigella and Salmonella comparative genomics available online at http://colibase.bham.ac.uk. Unlike other E.coli databases, which focus on the laboratory model strain K12, coliBASE is intended to reflect the full diversity of E.coli and its relatives. The database contains comparative data including whole genome alignments and lists of putative orthologous genes, together with numerous analytical tools and links to existing online resources. The data are stored in a relational database, accessible by a number of user-friendly search methods and graphical browsers. The database schema is generic and can easily be applied to other bacterial genomes. Two such databases, CampyDB (for the analysis of Campylobacter spp.) and ClostriDB (for Clostridium spp.) are also available at http://campy.bham.ac.uk and http://clostri.bham.ac.uk, respectively. An example of the power of E.coli comparative analyses such as those available through coliBASE is presented.